Cost effectiveness analysis of strategies for tuberculosis control in developing countries. Issue 7529 (10th November 2005) - Baltussen, Rob; Floyd, Katherine; Dye, Christopher
Abstract: Objective To assess the costs and health effects of tuberculosis control interventions in Africa and South East Asia in the context of the millennium development goals. Design Cost effectiveness analysis based on an epidemiological model. Setting Analyses undertaken for two regions classified by WHO according to their epidemiological grouping—Afr-E, countries in sub-Saharan Africa with very high adult and high child mortality, and Sear-D, countries in South East Asia with high adult and high child mortality. Data sources Published studies, costing databases, expert opinion. Main outcome measures Costs per disability adjusted life year (DALY) averted in 2000 international dollars (Int). Results Treatment of new cases of smear-positive tuberculosis in DOTS programmes cost Int6-8 per DALY averted in Afr-E and Int7 per DALY averted in Sear-D at coverage levels of 50-95%. In Afr-E, adding treatment of smear-negative and extra-pulmonary cases at a coverage level of 95% cost Int95 per DALY averted; the addition of DOTS-Plus treatment for multidrug resistant cases cost Int123. In Sear-D, these costs were Int52 and Int226, respectively. The full combination of interventions could reduce prevalence and mortality by over 50% in Sear-D between 1990 and 2010, and by almost 50% between 2000 and 2010 in Afr-E. Conclusions DOTS treatment of new smear-positive cases is the first priority in tuberculosis control, including in countries with high HIV prevalence. DOTS treatment of smear-negative and extra-pulmonary cases and DOTS-Plus treatment of multidrug resistant cases are also highly cost effective. To achieve the millennium development goal for tuberculosis control, substantial extra investment is needed to increase case finding and implement interventions on a wider scale.